Studying on the node’s influence and propagation path modes in microblogging - Hong YU; Xian YANG (Tongxin xuebao)
In order to analyze microblogging information propagation path modes,the node's influence to reflect its importance was defined based on considering the characteristics of information propagation in microblogging.Firstly,the broadcast/comment data of a microblogging was collected and preprocessed.Then,the formal description of the transmission network was given,and the node’s influence was defined which reflects its significance in the local and global aspects.The results of comparative experiments show that the new definition is reasonable.Besides,some information propagation path modes were proposed,which combine the measurement of influence.Finally,the results by using visualization software-NodeXL show that the information propagation path modes are typical.